Countryside education: Conceptual harmonization and historical evolution in Brazil - Silva, Giuliano Alves Borges e; Passador, João Luiz (Education Policy Analysis Archives, 2016)
Among academic studies it is common to distinguish “rural education” and “countryside education”, from the perspective that the emancipatory practice of the education must be based on the questioning of the individual and its relation with the world. Therefore, as an objective, this paper will: list differences and proximities through distinct categories of “rural” outside city life, such as remote rural or areas with proximity to the countryside, and; through literary, documental and law reviews, analyze public rural education policies in three distinctive historic periods and present a comparative framework between those eras. The conclusion suggests that social movements had broad participation in developing the concept of “countryside education” and the strength of those movements propelled an entire class of normative achievements. However, the challenges in maintaining quality and execution of the main breakthroughs still lingers on.